PERSEBARAN PRONOMINA PENUNJUK DALAM BAHASA MELAYU DI KALIMANTAN BARAT: KAJIAN GEOLINGUISTIK - Wiyanda, Syarifah Shafara; Asfar, Dedy Ary; Syahrani, Agus (Universitas Tanjungpura, 2024)
The research objectives is to describe the distribution of, pointer pronomina in Malay languages in West Kalimantan based on GIS. This research uses qualitative descriptive method. Criteria for selecting informants: aged 20